Faktor-faktor yang mempengaruhi realisasi penerimaan pajak bumi dan bangunan sektor pedesaan dan perkotaan di kabupaten Bangka Tengah - MEIRISKA FEBRIANTI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to examine the effect of the taxpayers, the population, the area, the amount of the building, gross regional domestic product towards the realization of property tax in Central Bangka District. The object of this research is property tax’s revenues received by the municipal governments of Central Bangka District. The population in this research is all of the villages in Central Bangka District which are 67 Villages. Samples that used in the research are 250 samples, from 50 Villages from 2010 to 2014. The data used in this research is secondary data. The result of this research are the number of taxpayers have an effect on realization of property tax, the number of population has an affect on the realization of property tax, the area has an effect on property tax, the building area has an effect on realization of property tax and the gross regional domestic product has no effect on realization of property tax.